Going native: Direct high throughput screening of secreted full-length IgG antibodies against cell membrane proteins. Issue 8 (17th November 2017) - Fang, Yongliang; Chu, Thach H.; Ackerman, Margaret E.; Griswold, Karl E.
ABSTRACT: Gel microdroplet – fluorescence activated cell sorting (GMD-FACS) is an innovative high throughput screening platform for recombinant protein libraries, and we show here that GMD-FACS can overcome many of the limitations associated with conventional screening methods for antibody libraries. For example, phage and cell surface display benefit from exceptionally high throughput, but generally require high quality, soluble antigen target and necessitate the use of anchored antibody fragments. In contrast, the GMD-FACS assay can screen for soluble, secreted, full-length IgGs at rates of several thousand clones per second, and the technique enables direct screening against membrane protein targets in their native cellular context. In proof-of-concept experiments, rare anti-EGFR antibody clones were efficiently enriched from a 10, 000-fold excess of anti-CCR5 clones in just three days. Looking forward, GMD-FACS has the potential to contribute to antibody discovery and engineering for difficult targets, such as ion channels and G protein-coupled receptors.